Violence against teachers of public elementary II schools - Garbin, Cléa Adas Saliba; Rovida, Tânia Adas Saliba; Costa, Adriana Alves; Garbin, Artênio José Isper (ARCHIVES OF HEALTH INVESTIGATION, 2016)
The aim of was to determine the prevalence of cases of violence against teachers, in public schools in a city in São Paulo State. This is a cross-sectional, analytical, quantitative and qualitative study. Being a total of 148 teachers and consenting answered a questionnaire. Of these, 109 agreed to participate, 43% reported having experienced some form of violence at school and of the affirmative cases, 85% said that verbal abuse is more common. It is concluded that violence is present in the school setting, due to various factors that leads to an inversion of values, which generates disrespect against teachers. Descriptors: Exposure to Violence; Education, Primary and Secondary; Adolescent.